Diversification of Orange Fruit Processing into Zero Waste-Based Wine Products in Pengejaran Village, Kintamani, Bangli - Sudiarta, I Wayan; Ni Luh Putu Putri, Setianingsih; Muliarta, I Nengah; Rustini, Ni Made; Lestarini, Asri; Purnomo, Amelia Putri; Prabandewi, Ni Luh Putu Ratih; Tiba, Andika Umbu (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Citrus fruits often experience overproduction, resulting in low prices, and even unmarketable fruit is frequently wasted. This innovation offers a sustainable solution through a zero-waste concept, where all parts of the citrus fruit, from the flesh and peel to the pulp, are optimally utilized. The program focuses on intensive training in producing high-quality orange wine, introducing proper fermentation techniques to create a high-value product. The orange peel and pulp, which are by-products of the winemaking process, are further processed into products such as jam, orange peel candy, or compost, so nothing is wasted. Community service not only provides farmers with new skills in creating innovative products but also teaches the principles of an environmentally friendly circular economy. The expected positive impacts include increased farmer incomes, new business opportunities, and more effective agricultural waste management, making Pengejaran Village a self-sustaining centre for processed citrus production. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production